(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
The study determined the profitability of cattle fattening in Maiduguri. Data were collected from a random sample of 300 fatteners using well-structured questionnaire. The data were analyzed using gross margin analysis and stochastic profit production function. Analysis of cost and returns revealed a mean gross margin per cattle of N46, 581.63 with cost of feed accounting for more than 83.9% of the average total variable cost per cattle. This suggests that cattle fattening is highly a profitable venture and that cost of feed is the most dominant variable cost of cattle fattening. All factors used in determining the impact of variable costs on profitability were found to be negative and significant except farm size which is positive. Thus, increase in farm size will lead to increase in profit all things being equal. The lack of incentives, ineffective extension services and poor credit facilities were major constraints identified for cattle fattening enterprise.